Phylogenetic relationships of Irkut and West Caucasian bat viruses within the Lyssavirus genus and suggested quantitative criteria based on the N gene sequence for lyssavirus genotype definition - Kuzmin, Ivan V.; Hughes, Gareth J.; Botvinkin, Alexandr D.; Orciari, Lillian A.; Rupprecht, Charles E. (Virus research, 2005)
The nucleoprotein (N), phosphoprotein (P) and glycoprotein (G) genes of Irkut and West Caucasian bat viruses (WCBV) were sequenced and compared with those of other lyssaviruses. N gene nucleotide identities provided unequivocal separation of all lyssavirus genotypes with an identity threshold of 82%. On this basis, Irkut virus should be considered as a new genotype with particular relatedness to genotypes 4 and 5 (78.0–78.6% identity for N gene nucleotides and 90.4–92.6% for amino acids). Furthermore, genotypes 4–6, together with Aravan, Khujand and Irkut viruses, present a solid phylogroup of Old World bat lyssaviruses. This relationship is apparent using all three viral genes, and causes overlap between intragenotype and intergenotype identities for the P gene (Aravan, Khujand viruses and genotype 6) and for the G gene (Aravan, Khujand, genotypes 5 and 6). WCBV is the most divergent of known lyssaviruses with only limited relatedness to genotypes 2 and 3.